Lingual bronchogenic cyst in a young child: A case report. Issue 1 (1st January 2018) - Gunnarsdottir, Agnes B.; Nilsson, Johan S.
Abstract: Choristomas, or foregut duplication cysts, are benign embryonic tumors characterized by normal tissue appearing in abnormal sites. If they are lined with respiratory epithelium they are termed bronchogenic cysts. When present, these rare lesions are usually intra-thoracic. We here present a case of a 4-year-old boy diagnosed with a bronchogenic cyst in the tongue.